Fertilization in Eucalyptus grandis on Severely Truncated Soil. II: Biomass Producnon - Prasad, K. G.; Gupta, G. N.; Singh, S. B.; Mohan, S.; Madhavan Nair, J.; Doe, A. D. (Indian Forester, 1984)
Biomass production of different components (root, stem, twig and leaf) of one year old Eucalyptus grandis due to different doses of urea and superphosphate application at Minmutti, Kerala, was assessed. Application of nitrogen and phosphorus increased biomass production of all tree components. Though, response was greater due to urea appliclltion than superphosphate application, combined application of N and P increased biomass production of all plant parts tremendously. Similar to biomass production fertilizer use efficiency was also better due to N and P application alone or in combination. Considering biomass production and fertilizer use efficieney, the treatment receiving 75 g urea along witb 73 g superphosphate found to be the most efficient treatment.